Chhau Dance: Cultural Trait of Purulia District, West Bengal, India - Bhutia, Namgyal Tshewang; Sinha, Sanghamitra; Sinha, Malavika (Journal of Studies on Art, Culture and Society, 2025)
In both political and legal spheres, culture is pervasive and fundamental to the human condition. Culture is the entirety of conduct and belief; it encompasses both normative and taught behaviour. The Chhau dance of Purulia, West Bengal, India, is included in the study. It's the dance of the earthen mask. The several kinds of drums are performed as background music in Chhau dance. It’s a self-defence martial art. The ancient Purulian people inherited Chhau dance. It's an athletic and acrobatic Indian dance that's done at Hindu festival. The various attributes of dance—the choreography, costume, and lyric patterns—have been discussed. The Chhau dance of Purulia is included on the list of intangible cultural heritage of UNESCO. The dance is distinct due to its rigorous training and accuracy, and it is a dance of heroic gesture. Purulia's Chhau dance is more specifically regional than community-specific. Instrumental music, dance, and martial arts are all combined in Chhau dance. It connects the various communities and their technical expertise and skills. The Chhau dance with conciliatory (with mask) actorish gestures is the cultural trait of Purulia, West Bengal.